Human Papillomavirus (HPV) Vaccine Coverage and Confidence in Italy: A Nationwide Cross-Sectional Study, the OBVIOUS Project - Marco Montalti; Aurelia Salussolia; Angelo Capodici; Francesca Scognamiglio; Zeno Di Valerio; Giusy La Fauci; Giorgia Soldà; Maria Pia Fantini; Anna Odone; Claudio Costantino; Julie Leask; Heidi J. Larson; et al. (Vaccines, 2024)
Background: Human Papillomavirus (HPV) vaccination rates are still below the target due to vaccine refusal or delay, lack of knowledge, and logistical challenges. Understanding these barriers is crucial for developing strategies to improve HPV vaccination rates. Methods: This cross-sectional study used a questionnaire to investigate social and behavioral factors influencing decision making about the HPV vaccine. The survey was conducted from 11 April to 29 May 2022 and involved 10,000 Italian citizens aged ≥ 18 years. The sample was stratified based on region of residence, gender, and age group. Results: 3160 participants were surveyed about themselves, while 1266 respondents were surveyed about their children’s vaccine uptake. Among females aged ≥ 26 years, the national average HPV vaccine uptake was 21.7%, with variations across different regions. In the 18–25 age group, females had a vaccine uptake (80.8%) twice as much as males (38.1%), while vaccine uptake among male and female children aged 9–11 was similar. Conclusions: The OBVIOUS study in Italy reveals factors influencing low HPV vaccine uptake, suggesting targeted approaches, tailored information campaigns, heightened awareness of eligibility, promoting early vaccination, addressing low-risk perception among males, addressing safety concerns, and enhancing perceived accessibility to improve vaccine uptake and mitigate health risks.